Implementasi Algoritme Acorn untuk Pengamanan Data pada Protokol MQTT menggunakan Perangkat Wemos ESP8266 - Mabda Amnesti Hananto; Ari Kusyanti; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Security attacks are threat that could happen on computer network. One of the attacks could happen on data transmission process. Cryptography could be the solution for securing the process of data transmission process. Acorn algorithm is a cryptography algorithm that guarantees two security aspects which are confidentiality and authentication. Acorn algorithm is implemented on devices that have a limited resource such as Wemos ESP8266 microcontroller. MQTT is a delivery protocol used in this research. The components of MQTT are publisher, subscriber and broker. Publisher sends ciphertext and tag to the broker according to the topic. Subscriber subscribs to the broker according to the topic for receiving ciphertext and tag. Test vector testing, encryption and decryption performance testing, also security testing is conducted to make sure the system is working properly. The average time result on encryption is 312.6 milliseconds, and decryption is 61.2 milliseconds. Security testing is conducted by doing an attack such as ciphertext-only attack and impersonation. The result of the security testing, Acorn algorithm has a security aspect that cannot be attacked or breached.